A single probe for imaging photons, electrons and physical forces. (5th May 2016) - Pilet, Nicolas; Lisunova, Yuliya; Lamattina, Fabio; Stevenson, Stephanie E; Pigozzi, Giancarlo; Paruch, Patrycja; Fink, Rainer H; Hug, Hans J; Quitmann, Christoph; Raabe, Joerg
Abstract: The combination of complementary measurement techniques has become a frequent approach to improve scientific knowledge. Pairing of the high lateral resolution scanning force microscopy (SFM) with the spectroscopic information accessible through scanning transmission soft x-ray microscopy (STXM) permits assessing physical and chemical material properties with high spatial resolution. We present progress from the NanoXAS instrument towards using an SFM probe as an x-ray detector for STXM measurements. Just by the variation of one parameter, the SFM probe can be utilised to detect either sample photo-emitted electrons or transmitted photons. This allows the use of a single probe to detect electrons, photons and physical forces of interest. We also show recent progress and demonstrate the current limitations of using a high aspect ratio coaxial SFM probe to detect photo-emitted electrons with very high lateral resolution. Novel probe designs are proposed to further progress in using an SFM probe as a STXM detector.